Medical care costs of newly diagnosed children with structural-metabolic epilepsy: a one year prevalence-based approached - Salih, Muhannad R.M.; Bahari, Mohd. Baidi; Shafie, Asrul Akmal; Ahmad Hassali, Mohamed Azmi; Baderaldeen , Omer Qutaiba; Abd, Arwa Y.; Ganesan, Vigneswari M. (Elsevier Inc., 2012)
Purpose